Public and private administration (2017)
Administration is a science that has been part of the history of mankind, is vital for the development not only of work and business life but also of life itself, as human beings should be surrounded by this concept for the Search and the achievement of the objectives and goals outlined, the essay will be able to find the two types of administration, a look at each of them, differences and / or similarities can be found, all this depends on the reader and The way in which they approach their reading, will expose the importance of each of the types of administration for the development of the state and how each of them contributes in its way to growth as a country, it will be understood how each one of them is important And that in the end they complement each other. Public administration and private administration must work together to make the state a prosperous state and every day better for each one of its members